Real - Time Data Ingestion Techniques - Rajeswari, Sangoju (Journal of Research in Science and Engineering, 2025)
Real-time data ingestion from diverse sources became an essential for businesses seeking to capture and analyze large volumes of data for immediate insights. Apache Flume, an open-source, distributed service designed for collecting, aggregating, and transporting streaming data, provides an efficient solution for real-time data ingestion in big data processing environments. This article explores the role of Apache Flume in enabling businesses to efficiently capture data from various sources, and Ingest it to big data processing systems.